On Weak-BCC-Algebras - Janus Thomys; Xiaohong Zhang (The Scientific World Journal)
We describe weak-BCC-algebras (also called BZ-algebras) in which the condition is satisfied only in the case when elements belong to the same branch. We also characterize ideals, nilradicals, and nilpotent elements of such algebras.